2016
DOI: 10.1016/j.fertnstert.2015.11.045
|View full text |Cite
|
Sign up to set email alerts
|

Western-style diet, with and without chronic androgen treatment, alters the number, structure, and function of small antral follicles in ovaries of young adult monkeys

Abstract: Objective To examine the small antral follicle (SAF) cohort in ovaries of adult rhesus monkeys following consumption of a western-style diet (WSD), with or without chronically elevated androgen levels since before puberty. Design Cholesterol or testosterone (T; n=6/group) implants were placed subcutaneously in female rhesus macaques beginning at 1 yr of age (pre-pubertal), with addition of a WSD (high fat/fructose) at 5.5 yrs (menarche ~2.6 yrs). Ovaries were collected at 7 yrs of age. One ovary/female was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 52 publications
(92 reference statements)
3
15
0
Order By: Relevance
“…When main effects are significant, different lower case letters indicate significant differences between individual groups; asterisks (* vs **) denote trend towards differences. When no symbols are present, there were no differences detected by pairwise comparisons androgen (~6 years) [41,42]. In this previous study, we also observed increased numbers of atretic small antral follicles in vivo and increased numbers of degenerating oocytes following follicle culture after WSD and T+WSD treatments.…”
Section: Discussionsupporting
confidence: 49%
“…When main effects are significant, different lower case letters indicate significant differences between individual groups; asterisks (* vs **) denote trend towards differences. When no symbols are present, there were no differences detected by pairwise comparisons androgen (~6 years) [41,42]. In this previous study, we also observed increased numbers of atretic small antral follicles in vivo and increased numbers of degenerating oocytes following follicle culture after WSD and T+WSD treatments.…”
Section: Discussionsupporting
confidence: 49%
“…Ovarian structure in the early follicular phase (Days 1-3; ovarian size, number of antral follicles, antral follicle location within the ovary) was analyzed in all females (n = 10/group) by 3D/4D Doppler ultrasound (GE Voluson 730 Expert, GE Healthcare, Milwaukee, WI, USA) under ketamine sedation (10 mg/kg) using previously validated methods (Bishop et al, 2009;McGee et al, 2014). Polycystic ovarian morphology (PCOM) was determined for each ovary using defined characteristics (Bishop et al, 2016). Near the mid-cycle E2 surge and again at mid-luteal phase (6-8 days post-LH surge), a subset of monkeys (n = 6/group) were sedated with ketamine and placed under inhaled isoflurane anesthesia (1.5% isoflurane mixed with 100% oxygen at a flow rate of 1.5 l/min; Portable Anesthesia Machine, Patterson Veterinary Supply, Inc. Greeley, CO, USA).…”
Section: Ultrasound Analysesmentioning
confidence: 99%
“…An important question then is discerning how putative causative factors, such as elevated T or metabolic perturbations, interact to produce PCOS symptoms. In our recent pilot study (McGee et al, 2014;Bishop et al, 2016), combined administration of T with an obesogenic westernstyle diet (WSD) decreased insulin sensitivity and altered features of ovarian function in female rhesus monkeys. Although the protocol provided intriguing evidence for some PCOS-like effects of chronic T+WSD treatment, it was limited in experimental design and unable to distinguish effects of T or WSD alone, or if the effects of T and WSD were additive or synergistic.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, determining whether a similar proinflammatory follicular microenvironment, embryonic arrest, and differential gene expression, which is observed when the females are on a WSD for a longer period of time (i.e., more than a year of continual WSD consumption) and develop metabolic dysfunction, should also be determined. We note that there are already published findings of adverse effects from long-term WSD consumption on rhesus macaque ovarian and uterine structure and function ( 82 , 83 ), but — to our knowledge — there are not yet studies on oocyte fertilization and preimplantation development during COS cycles; this is a current research focus of our group. The results of these studies will help determine the precise impact of WSD on infertility and its confounding effects on IVF success ( 8 , 84 ).…”
Section: Discussionmentioning
confidence: 93%